PENGARUH DISKONTINUITAS MASSA BATUAN VOLKANIK TERHADAP STABILITAS LERENG DI DAERAH JELAPAN DAN SEKITARNYA, KECAMATAN PUNDONG, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Arie Noor Rakhman; Nur Widi Astanto Agus Triheriyadi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
This research is intended to know the effect of discontinuity on the mass of volcanic rock for rock slope stability. The study sites are located at Jelapan area and its surrounding, Pundong District, Bantul Regency, Special Region of Yogyakarta. With stability assessments of rock slopes, it can be used to identify potential disasters of rock mass movement, direction of movement and recommendations for disaster risk minimization. Analysis of the continuity on the mass of volcanic rock using rock mass classification of rock mass rating system (RMR) (Bieniawski, 1989). The data used are physical properties, index properties, mechanical properties, orientation of joint position and rock slope. The synthesis of data is done mainly on morphological data, stratigraphy, geological structure to know the control of geological condition on the stability of volcanic rock slope in research area. Based on the calculation of the rock mass classification of RMR, the cliff at 7°59’20,88” LS 110°19’19,09” BT is 28 which is considered poor. The RMR value is controlled by intensive joints that dominate with joint spacing less than 60 mm; the condition of the surface of the joint field is smooth and continuous, estrangement joint 1 - 5 mm, slightly weathered with a value RQD 43.37%. Rock mass that collapses and landslides are lava and andesite breccia. The rock fall occurs following the slope of the planar plane of the platy joint structure and the rock contact N170°E/32°. It is interpreted by the initial stress control with high anisotropic stress at the edge of the slope.